Pharmacokinetics and bioavailability of midazolam in rats following single dose administration of intravenous solution, intranasal dispersion, and in situ nasal gel - Elahehnaz Parhizkar, Saba Movaffagh, Shohreh Alipour (Journal of Applied Pharmaceutical Science, 2021)
Midazolam (MDZ) is used as a sedative and anxiolytic agent in pediatric operations or dentistry procedures. Considering low solubility in physiologic pH, commercial intravenous MDZ formulation is constructed as an acidic solution, which is unofficially used orally, rectally, buccally, and intranasally in spite of low patient compliance due to irritation, inflammation, and caustic effect at administration sites. Due to the pathological safety of our previously designed MDZ poloxamer nasal gel (MDZ-PLX-GEL), its pharmacokinetic parameters were determined and compared to MDZ aqueous dispersion (MDZ-DIS) after intranasal administration in rats. MDZ-PLX-GEL was prepared using PLX (22% w/v), MDZ (1% w/v), and propylene glycol (10% v/v) in phosphate buffer pH 6. For better comparison, the commercial intravenous solution was evaluated as well. MDZ was analyzed using a validated high-performance liquid chromatography method. Male Sprague Dawley rats were used for in vivo experiments. The most important feature of MDZ-PLX-GEL was a rapid onset (20 minutes) with a mean residence time (MRT) of 170 minutes, which means MDZ effective blood concentration (100–200 ng/ml) lasts 3 hours which could increase MDZ-PLX-GEL absolute bioavailability up to 66.5%±4.6%. It was confirmed that the thermosensitive poloxamer gel was a suitable nasal carrier for MDZ that could increase its residence time, which may be a proper alternative for the currently unofficial routes of MDZ administration.
Keywords: Midazolam, intranasal delivery, poloxamer gel, pharmacokinetics.